TO THE MATTER OF STABILIZATION OF SADDLES OF PUNCH MILLS - I. O. Sazonenko; V. A. Zemtsov; A. N. Yurchak (Литьë и металлургия, 2012)
The methods of increasing the resistance of one-piece male punches piercing mills are reviewed.